Telemedicine in Spine Surgery: Global Perspectives and Practices. Issue 5 (June 2023) - Riew, Grant J.; Lovecchio, Francis; Samartzis, Dino; Louie, Philip K.; Germscheid, Niccole; An, Howard; Cheung, Jason Pui Yin; Chutkan, Norman; Mallow, Gary Michael; Neva, Marko H.; Phillips, Frank M.; Sciubba, Daniel; et al.
Study Design: Cross-sectional, anonymous, international survey. Objectives: The COVID-19 pandemic has resulted in the rapid adoption of telemedicine in spine surgery. This study sought to determine the extent of adoption and global perspectives on telemedicine in spine surgery. Methods: All members of AO Spine International were emailed an anonymous survey covering the participant's experiences with and perceptions of telemedicine. Descriptive statistics were used to depict responses. Responses were compared among regions. Results: 485 spine surgeons participated in the survey. Telemedicine usage rose from <10.0% to >39.0% of all visits. A majority of providers (60.5%) performed at least one telemedicine visit. The format of "telemedicine" varied widely by region: European (50.0%) and African (45.2%) surgeons were more likely to use phone calls, whereas North (66.7%) and South American (77.0%) surgeons more commonly used video ( P < 0.001). North American providers used telemedicine the most during COVID-19 (>60.0% of all visits). 81.9% of all providers "agreed/strongly agreed" telemedicine was easy to use. Respondents tended to "agree" that imaging review, the initial appointment, and postoperative care could be performed using telemedicine. Almost all (95.4%) surgeons preferred at least one in-person visit prior to the day of surgery. Conclusion: Our study noted significant geographical differences in the rate of telemedicine adoption and the platform of telemedicine utilized. The results suggest a significant increase in telemedicine utilization, particularly in North America. Spine surgeons found telemedicine feasible for imaging review, initial visits, and follow-up visits although the vast majority still preferred at least one in-person preoperative visit.